Development of the system for multichannel microwave plasma probing in the torsatron U-2M - Berezhnyj, V.L.; Ocheretenko, V.L.; Pinos, I.B.; Skibenko, A.I.; Prokopenko, A.V.; Larin, Yu.V.; Maznichenko, S.M.; Sitnikov, D.A.; Tarasov, M.I. (Вопросы атомной науки и техники, 2009)
To study successfully the conditions for production and heating of the plasma, its dynamics in the process of an RF discharge in the torsatron U-2M, a multichannel system for microwave diagnostics is suggested. To obtain the electron density profiles with an asymmetric plasma cross-section in the l=2 torsatron, 5 fan channels and 3 longitudinal channels will be used. For these measurements a quadrature interferometer at a frequency of 140 GHz is under development.